CaMKII Is Essential for the Function of the Enteric Nervous System - Gao, Na; Luo, Jialie; Uray, Karen; Qian, Aihua; Yin, Shijin; Wang, Guodu; Wang, Xiyu; Xia, Yun; Wood, Jackie D.; Hu, Hongzhen (PLOS ONE, 2012)
Background Ca2+/calmodulin-dependent protein kinases (CaMKs) are major downstream mediators of neuronal calcium signaling that regulate multiple neuronal functions. CaMKII, one of the key CaMKs, plays a significant role in mediating cellular responses to external signaling molecules. Although calcium signaling plays an essential role in the enteric nervous system (ENS), the role of CaMKII in neurogenic intestinal function has not been determined. In this study, we investigated the function and expression pattern of CaMKII in the ENS across several mammalian species. Methodology/Principal Findings CaMKII expression was characterized by immunofluorescence analyses and Western Blot. CaMKII function was examined by intracellular recordings and by assays of colonic contractile activity. Immunoreactivity for CaMKII was detected in the ENS of guinea pig, mouse, rat and human preparations. In guinea pig ENS, CaMKII immunoreactivity was enriched in both nitric oxide synthase (NOS)- and calretinin-containing myenteric plexus neurons and non-cholinergic secretomotor/vasodilator neurons in the submucosal plexus. CaMKII immunoreactivity was also expressed in both cholinergic and non-cholinergic neurons in the ENS of mouse, rat and human. The selective CaMKII inhibitor, KN-62, suppressed stimulus-evoked purinergic slow EPSPs and ATP-induced slow EPSP-like response in guinea pig submucosal plexus, suggesting that CaMKII activity is required for some metabotropic synaptic transmissions in the ENS. More importantly, KN-62 significantly suppressed tetrodotoxin-induced contractile response in mouse colon, which suggests that CaMKII activity is a major determinant of the tonic neurogenic inhibition of this tissue. Conclusion ENS neurons across multiple mammalian species express CaMKII. CaMKII signaling constitutes an important molecular mechanism for controlling intestinal motility and secretion by regulating the excitability of musculomotor and secretomotor neurons. These findings revealed a fundamental role of CaMKII in the ENS and provide clues for the treatment of intestinal dysfunctions.